Dematerialization of administrative documents in Morocco: legal and regulatory framework - Mariam MAKKOUDI; Noureddine ELMQADDEM; Édouard VASSEUR (Journal of Information Sciences, 2022)
The digital world has clearly changed the way documents are produced, stored and communicated within organizations. Thus, public administrations are implementing plans to dematerialize all or part of their work processes, and consequently their administrative documents (records). This paper aims to provide a reading of the Moroccan legal and regulatory corpus dealing with dematerialization. This analysis was approached according to three types of reading: a chronological reading, a reading according to the life cycle of administrative documents (records), and a functional reading. Thus, the approach revealed the interest granted by the Moroccan legislator to the dematerialization project within public services, as shown by the number and variety of regulatory texts that have approached this project.